Circular Economy Implementation: A Case Study in Indonesia - Mulyani, Fransiska; Frian, Antonio; Khairal Abdullah, Tengku Mohd. (Jurnal Inovasi Global, 2024)
Circular economy has become a trend as an approach in many countries to achieve sustainability. Indonesia as one of the most populous countries also implement Circular Economy for environmental purpose. The number of research publication has been increasing for the past several years in Indonesia, however review of such publication from the perspective of SLR (Systematic Literature Review) has been lacking. This research will identify and illustrate how far the circular economy implementation has been done in Indonesia. This research applies systematic literature review, mapping analysis, and bibliometric analysis to answer the gap. The database in this research based on Scopus Indexed publication from 31.453 publication, in which this research successfully extracted 35 publications. The key findings in this research were Circular Economy implementation in Indonesia mainly on Agriculture and Household sector within Java Island by using reduce, reuse, recycle strategy dominantly. The bibliometric analysis shown that there is strong relationship between circular economy implementation and waste management that gave impact on sustainability. This research reveals the research gap for circular economy by geographical, strategy, and topics as potential future research. This research carries some weight to support Indonesia future implementation on Circular Economy.